GAYA MANGA DALAM KOMIK GARUDAYANA KARYA IS YUNIARTO - Dhevi Enlivena IRM (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article is the result of research on the manga style comic Garudayana. This departs from the reality on the ground that inthe last decade the Japanese comics or manga translation once mastered and favored market. However, one of the Indonesianlocal comics, which is able to penetrate the ranks of comic Garudayana translation, and has sales nearly match the success ofJapanese comic translation. It becomes background research on comics Garudayana especially in terms of style of drawing andcomic storytelling style. This study uses the concept of interpretation analysis using McCloud manga storytelling techniques,combined with the power of thought Darmawan over manga. The results of this study are of the form Garudayanacomic style character expression, the transition between panels and word balloons shapes, have a tendency to follow themanga style now favored by the people of Indonesia.Keyword : Manga,comic, Garudayana, Is Yuniarto